A facile slow-gel method for bulk Al-doped carboxymethyl cellulose aerogels with excellent flame retardancy. (1st March 2019) - Hu, Wenbin; Lu, Lingbin; Li, Zhanying; Shao, Lin
Highlights: Bulk Al-doped carboxymethyl cellulose aerogels were fabricated via a facile slow-gel method and freeze-drying technology. Compared with pure silica aerogels, the Al-doped carboxymethyl cellulose aerogels possed better weight-bearing capacity. The Al-doped CMC aerogels exhibited excellent flame retardancy and could be rated V-0 regarding UL-94 testing. Abstract: Bulk Al-doped carboxymethyl cellulose aerogels were obtained via a facile slow-gel method and freeze-drying technology. In this method, the cross-linker Al 3+ was released slowly and completely with enough d -(+)-gluconic acid δ -lactone as a sustained-release agent. Depended on controlled releasing of Al 3+, the reaction speed between Al 3+ and carboxyl groups was controlled and Al 3+ was well-distributed in the aerogels. The coordination type between Al 3+ and carboxymethyl cellulose was the bidentate bridging coordination. By adjusting the amount of Al 3+ and the degree of substitution of carboxymethyl cellulose, interconnected network and closely packed sheet-like structure presented, respectively. According to the nitrogen adsorption-desorption isotherms, the aerogels were a kind of mesoporous material with pore blocking or cavitation. In addition, the aerogels exhibited outstanding weight-bearing capacity and excellent flame retardancy. This work provided a valuable reference for doping metal ions into polysaccharide aerogels and expanding the application fields of aerogels.